Electrolysis cell
The electrolytic cell addresses uneven reduction in the hydrogen electrode layer by using a NiO-ceramic layer with controlled dimensions and porosity, and a metal support with a specific aperture ratio to uniformly supply reducing gas, thereby preventing cracks.
Patent Information
- Application Number
- JP2023108158
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-30
- Publication Date
- 2025-01-17
AI Technical Summary
In metal support type electrolytic cells, uneven reduction of NiO to Ni in the hydrogen electrode layer leads to dimensional changes, potentially causing cracks due to differential supply of reducing gas through communication holes.
The electrolytic cell design includes a hydrogen electrode layer composed of NiO and ceramic material, with controlled dimensions and porosity, and a metal support with a specific aperture ratio to ensure uniform gas supply, reducing the difference in dimensional changes across the layer.
This design suppresses cracks in the hydrogen electrode layer by ensuring uniform reduction and minimal dimensional changes, enhancing the cell's structural integrity.
Smart Images

Figure 2025007029000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an electrolysis cell. [Background technology]
[0002] 2. Description of the Related Art Metal support type electrolysis cells having a cell body disposed on a metal support are known (see, for example, Patent Document 1).
[0003] The metal support has a plurality of communication holes formed in its main surface. The cell main body is formed on the main surface of the metal support and has a hydrogen electrode layer covering the plurality of communication holes, an oxygen electrode layer, and an electrolyte layer disposed between the hydrogen electrode layer and the oxygen electrode layer. The hydrogen electrode layer contains nickel. The nickel contained in the hydrogen electrode layer becomes nickel oxide (NiO) in an oxidizing atmosphere and becomes metallic nickel (Ni) in a reducing atmosphere. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent Publication No. 2020-155337 Summary of the Invention [Problem to be solved by the invention]
[0005] In order to impart electrical conductivity to the hydrogen electrode layer, it is necessary to reduce the NiO contained in the hydrogen electrode layer to Ni by carrying out a heat treatment (hereinafter referred to as a "reduction treatment") in which a reducing gas is supplied at high temperature.
[0006] However, in a metal-supported electrolytic cell, while the reducing gas is easily supplied to the portion of the hydrogen electrode layer that is located directly above the communicating hole, the reducing gas is difficult to supply to the portion of the hydrogen electrode layer other than the directly above portion that is not in contact with the communicating hole.
[0007] Therefore, in the directly above portion, the reduction of NiO progresses and dimensional changes are likely to occur, whereas in the non-directly above portion, the reduction of NiO does not progress and dimensional changes are unlikely to occur. As a result, there is a risk of cracks occurring between the directly above portion and the non-directly above portion.
[0008] An object of the present invention is to provide an electrolysis cell capable of suppressing the occurrence of cracks in a hydrogen electrode layer. [Means for solving the problem]
[0009] An electrolysis cell according to a first aspect of the present invention includes a metal support and a cell main body. The metal support has a plurality of communication holes formed in a main surface. The cell main body includes a hydrogen electrode layer formed on the main surface and covering the plurality of communication holes, an oxygen electrode layer, and an electrolyte layer disposed between the hydrogen electrode layer and the oxygen electrode layer. The hydrogen electrode layer is composed of NiO and a ceramic material. When the dimension at room temperature of the hydrogen electrode layer in a reduced state obtained by subjecting the hydrogen electrode layer to a heat treatment in a reducing atmosphere at 750°C is L2, and the dimension at room temperature of the hydrogen electrode layer in a non-reduced state that has not been subjected to the heat treatment is L1, the amount of change is ΔL=L2-L1, where (ΔL / L1)×100 is within ±0.05%.
[0010] An electrolysis cell according to a second aspect of the present invention is related to the first aspect, wherein the opening ratio of the plurality of communicating holes in the main surface is 5% or more.
[0011] An electrolytic cell according to a third aspect of the present invention is related to the first or second aspect, wherein the porosity of the hydrogen electrode layer in the non-reduced state is 16% or more. Effect of the Invention
[0012] According to the present invention, it is possible to provide an electrolysis cell capable of suppressing the occurrence of cracks in the hydrogen electrode layer. [Brief description of the drawings]
[0013] [Figure 1]FIG. 1 is a cross-sectional view of an electrolysis cell according to an embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] (Electrolysis cell 1) 1 is a cross-sectional view of an electrolysis cell 1 according to an embodiment. The electrolysis cell 1 is a so-called metal support type electrolysis cell.
[0015] As shown in FIG. 1, the electrolysis cell 1 includes a metal support 10, a cell main body 20, and a flow path member 30.
[0016] [Metal support 10] The metal support 10 supports the cell main body 20. The metal support 10 is formed in a plate shape. The metal support 10 may be in the shape of a flat plate or a curved plate.
[0017] The metal support 10 is not particularly limited as long as it can support the electrolytic cell 1, and the thickness thereof can be, for example, 0.1 mm or more and 2.0 mm or less.
[0018] The metal support 10 has a plurality of communicating holes 11 , a first main surface 12 and a second main surface 13 .
[0019] Each communication hole 11 penetrates the metal support 10 from the first main surface 12 to the second main surface 13. Each communication hole 11 opens to both the first main surface 12 and the second main surface 13. The opening of each communication hole 11 on the first main surface 12 side is covered by the hydrogen electrode layer 6. The opening of each communication hole 11 on the second main surface 13 side is connected to a flow path 30a described later.
[0020] Each communication hole 11 can be formed by mechanical processing (for example, punching), laser processing, chemical processing (for example, etching), or the like.
[0021] In this embodiment, each communication hole 11 is formed linearly along the Z-axis direction. However, each communication hole 11 may be inclined with respect to the Z-axis direction, and may not be linear. Furthermore, the communication holes 11 may be connected to each other.
[0022] The first main surface 12 is provided on the opposite side to the second main surface 13. A cell main body 20 is disposed on the first main surface 12. A flow path member 30 is bonded to the second main surface 13.
[0023] The opening ratio of the plurality of communication holes 11 in the first main surface 12 is preferably 5% or more. This allows the reducing gas to be uniformly supplied to the hydrogen electrode layer 6 (described later) through each communication hole 11, thereby reducing uneven reduction in the hydrogen electrode layer 6. As a result, the reduction in uneven reduction in the hydrogen electrode layer 6 can be reduced, thereby suppressing the occurrence of cracks in the hydrogen electrode layer 6.
[0024] The aperture ratio is calculated by dividing the total open area of the plurality of communication holes 11 in a plan view of the first main surface 12 by the area of the region of the first main surface 12 covered by the hydrogen electrode layer 6.
[0025] The metal support 10 is made of a metal material. For example, the metal support 10 is made of an alloy material containing Cr (chromium). Examples of such metal materials include Fe-Cr alloy steel (stainless steel, etc.) and Ni-Cr alloy steel. The Cr content of the metal support 10 is not particularly limited, but can be set to 4% by mass or more and 30% by mass or less.
[0026] The metal support 10 may contain Ti (titanium) and / or Al (aluminum). The Ti content in the metal support 10 is not particularly limited, but may be 0.01 mol% or more and 1.0 mol% or less. The Al content in the metal support 10 is not particularly limited, but may be 0.01 mol% or more and 0.4 mol% or less. The metal support 10 may contain Ti as TiO2 (titania) or Al as Al2O3 (alumina).
[0027] The metal support 10 may have an oxide film on its surface, which is formed by oxidation of the constituent elements of the metal support 10. A typical example of the oxide film is a chromium oxide film. The chromium oxide film covers at least a portion of the surface of the metal support 10. The chromium oxide film may also cover at least a portion of the inner wall surface of each of the communicating holes 11.
[0028] [Cell body 20] The cell body 20 is disposed on the metal support 10. The cell body 20 is supported by the metal support 10. The cell body 20 has a hydrogen electrode layer 6 (cathode), an electrolyte layer 7, a reaction prevention layer 8, and an oxygen electrode layer 9 (anode).
[0029] The hydrogen electrode layer 6, electrolyte layer 7, reaction prevention layer 8, and oxygen electrode layer 9 are laminated in this order in the Z-axis direction from the metal support 10 side. The hydrogen electrode layer 6, electrolyte layer 7, and oxygen electrode layer 9 are essential components, while the reaction prevention layer 8 is optional.
[0030] [Hydrogen electrode layer 6] The hydrogen electrode layer 6 is disposed between the metal support 10 and the electrolyte layer 7. The hydrogen electrode layer 6 is formed on a first main surface 12 of the metal support 10. As shown in FIG. 1 , in this embodiment, the hydrogen electrode layer 6 is embedded in each of the communicating holes 11 of the metal support 10, but the hydrogen electrode layer 6 does not have to be embedded in each of the communicating holes 11 of the metal support 10.
[0031] A source gas is supplied to the hydrogen electrode layer 6 through each of the communication holes 11. The source gas contains at least H2O.
[0032] When the raw material gas contains only H2O, the hydrogen electrode layer 6 produces H2 from the raw material gas in accordance with the electrochemical reaction of water electrolysis shown in the following formula (1).
[0033] Hydrogen electrode layer 6: H2O+2e - →H2+O 2- (1)
[0034] When the raw gas contains CO in addition to H2O, the hydrogen electrode layer 6 converts H2, CO, and O2 from the raw gas in accordance with the electrochemical reactions of co-electrolysis shown in the following formulas (2), (3), and (4). 2- Generate.
[0035] Hydrogen electrode layer 6: CO2+H2O+4e - →CO+H2+2O 2- (2) Electrochemical reaction of H2O: H2O+2e - →H2+O 2- (3) Electrochemical reaction of CO2: CO2+2e - →CO+O 2- (4)
[0036] The hydrogen electrode layer 6 is a porous body having electronic conductivity and is made of nickel oxide (NiO) and a ceramic material.
[0037] Examples of ceramic materials that can be used include Y2O3, YSZ, CSZ, ScSZ, GDC, SDC, (La,Sr)(Cr,Mn)O3, (La,Sr)TiO3, Sr2(Fe,Mo)2O6, (La,Sr)VO3, (La,Sr)FeO3, LDC (lanthanum doped ceria), LSGM (lanthanum gallate), and mixed materials of two or more of these.
[0038] The volume ratio of NiO to the entire volume of the hydrogen electrode layer 6 (excluding the volume of the space occupied by the pores) can be 35 volume % or more and 55 volume % or less, calculated as Ni. The volume ratio of the ceramic material to the entire volume of the hydrogen electrode layer 6 (excluding the volume of the space occupied by the pores) can be 45 volume % or more and 65 volume % or less. The volume ratios of NiO and the ceramic material are measured in a non-reduced state that has not been subjected to the reduction treatment described below.
[0039] The porosity of the hydrogen electrode layer 6 is not particularly limited, but can be, for example, 10% to 40% in a non-reduced state described below. The porosity of the hydrogen electrode layer 6 is preferably 16% or more in a non-reduced state. This allows the reducing gas described below to easily diffuse into the hydrogen electrode layer 6, thereby reducing uneven reduction in the hydrogen electrode layer 6. As a result, the reduction unevenness in the hydrogen electrode layer 6 is reduced, and the occurrence of cracks in the hydrogen electrode layer 6 can be suppressed.
[0040] The porosity of the hydrogen electrode layer 6 is calculated by the following method. First, a cross section of the hydrogen electrode layer 6 along the Z-axis direction is exposed. Next, a backscattered electron image of the cross section of the hydrogen electrode layer 6 is obtained at 10,000 times magnification using an SEM device (FE-SEM JSM-7900F, manufactured by JEOL Ltd.). Next, the portions displayed in black in the backscattered electron image (corresponding to pores) are identified using image analysis software Image-Pro manufactured by MEDIACYBERNETICS. The porosity of the hydrogen electrode layer 6 is calculated by dividing the total area of the pores by the total area of the backscattered electron images of the hydrogen electrode layer 6.
[0041] The thickness of the hydrogen electrode layer 6 is not particularly limited, but may be, for example, 5 μm or more and 400 μm or less.
[0042] The method for forming the hydrogen electrode layer 6 is not particularly limited, and may be a firing method, a spray coating method (such as a thermal spray method, an aerosol deposition method, an aerosol gas deposition method, a powder jet deposition method, a particle jet deposition method, or a cold spray method), a PVD method (such as a sputtering method or a pulsed laser deposition method), or a CVD method.
[0043] Here, in order to impart electrical conductivity to the hydrogen electrode layer 6, it is necessary to reduce the NiO contained in the hydrogen electrode layer 6 to Ni by carrying out a heat treatment (hereinafter referred to as a "reduction treatment") in which a reducing gas is supplied to the hydrogen electrode layer 6 at a high temperature.
[0044] The reduction of NiO to Ni causes a dimensional change in the hydrogen electrode layer 6. At this time, the reducing gas is easily supplied to the directly above portion of the hydrogen electrode layer 6 located directly above the communicating hole 11, while the reducing gas is not easily supplied to the non-directly above portion of the hydrogen electrode layer 6 other than the directly above portion. Therefore, the reduction of NiO progresses in the directly above portion, causing a dimensional change, whereas the reduction of NiO does not progress in the non-directly above portion, causing a dimensional change. As a result, there is a risk of cracks occurring between the directly above portion and the non-directly above portion. Therefore, in the electrolysis cell 1 according to this embodiment, the dimensional change in the hydrogen electrode layer 6 caused by the reduction of NiO to Ni is reduced as follows.
[0045] In this embodiment, a "reduction treatment" is performed on the hydrogen electrode layer 6 by supplying a reducing gas at 750° C. for three hours. By this reduction treatment, NiO contained in the hydrogen electrode layer 6 is reduced to Ni, and the hydrogen electrode layer 6 changes from a non-reduced state to a reduced state.
[0046] In this case, when the dimension of the hydrogen electrode layer 6 in a non-reduced state at room temperature is L1, the dimension of the hydrogen electrode layer 6 in a reduced state at room temperature is L2, and the amount of change therebetween is ΔL=L2-L1, (ΔL / L1)×100 is within ±0.05% (i.e., −0.05% or more and +0.05% or less). This makes it possible to reduce the difference in dimensional change between the directly-overlying portion and the non-directly-overlying portion of the hydrogen electrode layer 6, thereby suppressing the occurrence of cracks between the directly-overlying portion and the non-directly-overlying portion.
[0047] The "dimension" refers to the thickness of the hydrogen electrode layer 6, the representative length of the shape of the hydrogen electrode layer 6 in a planar view (the diameter in the case of a circle, the length of one side in the case of a square, and the length of the long side in the case of a rectangle), etc.
[0048] ΔL can be controlled by adjusting at least one of the average particle size ratio of NiO to the ceramic material, the volume ratio of NiO, and the volume ratio of the ceramic material. When the average particle size of NiO is R1 and the average particle size of the ceramic material is R2, the value of the average particle size ratio R2 / R1 is not particularly limited, but can be, for example, 0.1 or more and 1.5 or less. The average particle size ratio R2 / R1 is a measurement value in a non-reduced state that has not been subjected to reduction treatment.
[0049] The average particle size ratio R2 / R1 of NiO and ceramic material can be obtained by the following method. First, the surface of the hydrogen electrode layer 6 is polished, and then the surface of the hydrogen electrode layer 6 is thermally etched to clarify the grain boundaries between NiO particles and ceramic particles. Next, a SEM (scanning electron microscope) image of the surface of the hydrogen electrode layer 6 is obtained at a magnification that can accommodate a total of about 150 NiO particles and ceramic particles. Next, the SEM image is analyzed to determine the total area and number of all NiO particles, and the total area and number of all ceramic particles. Then, the average particle size R1 of NiO is calculated by dividing the total area of all NiO particles by the number of particles, and the average particle size R2 of the ceramic material is calculated by dividing the total area of all ceramic particles by the number of particles. Then, the average particle size ratio R2 / R1 is calculated by dividing the average particle size R2 by the average particle size R1.
[0050] [Electrolyte layer 7] The electrolyte layer 7 is disposed between the hydrogen electrode layer 6 and the oxygen electrode layer 9. In this embodiment, the reaction prevention layer 8 is disposed between the electrolyte layer 7 and the oxygen electrode layer 9, so that the electrolyte layer 7 is sandwiched between the hydrogen electrode layer 6 and the reaction prevention layer 8.
[0051] The electrolyte layer 7 covers the hydrogen electrode layer 6 and also covers a region of the first main surface 12 of the metal support 10 that is exposed from the hydrogen electrode layer 6 .
[0052] The electrolyte layer 7 is formed by discharging the O 2-to the oxygen electrode layer 9. The electrolyte layer 7 is made of a dense material having oxide ion conductivity. The electrolyte layer 7 can be made of, for example, YSZ (yttria-stabilized zirconia, e.g., 8YSZ), GDC (gadolinium-doped ceria), ScSZ (scandia-stabilized zirconia), SDC (samarium-doped ceria), LSGM (lanthanum gallate), or the like.
[0053] The porosity of the electrolyte layer 7 is not particularly limited, but may be, for example, 0.1% to 7%. The thickness of the electrolyte layer 7 is not particularly limited, but may be, for example, 1 μm to 100 μm.
[0054] The method for forming the electrolyte layer 7 is not particularly limited, and a baking method, a spray coating method, a PVD method, a CVD method, or the like can be used.
[0055] [Reaction prevention layer 8] The reaction prevention layer 8 is disposed between the electrolyte layer 7 and the oxygen electrode layer 9. The reaction prevention layer 8 is disposed on the opposite side of the electrolyte layer 7 to the hydrogen electrode layer 6. The reaction prevention layer 8 prevents the constituent elements of the electrolyte layer 7 from reacting with the constituent elements of the oxygen electrode layer 9 to form a layer with high electrical resistance.
[0056] The reaction prevention layer 8 is made of an oxide ion conductive material, and may be made of GDC, SDC, or the like.
[0057] The porosity of the reaction prevention layer 8 is not particularly limited, but may be, for example, 0.1% to 50%. The thickness of the reaction prevention layer 8 is not particularly limited, but may be, for example, 1 μm to 50 μm.
[0058] The method for forming the reaction prevention layer 8 is not particularly limited, and a baking method, a spray coating method, a PVD method, a CVD method, or the like can be used.
[0059] [Oxygen electrode layer 9] The oxygen electrode layer 9 is disposed on the opposite side of the hydrogen electrode layer 6 with respect to the electrolyte layer 7. In this embodiment, since the reaction prevention layer 8 is disposed between the electrolyte layer 7 and the oxygen electrode layer 9, the oxygen electrode layer 9 is connected to the reaction prevention layer 8. If the reaction prevention layer 8 is not disposed between the electrolyte layer 7 and the oxygen electrode layer 9, the oxygen electrode layer 9 is connected to the electrolyte layer 7.
[0060] The oxygen electrode layer 9 reacts with O 2 transferred from the hydrogen electrode layer 6 through the electrolyte layer 7 in accordance with the chemical reaction of the following formula (2): 2- produces O2 from
[0061] Oxygen electrode layer 9:2O 2- →O2+4e - (2)
[0062] The oxygen electrode layer 9 is made of a porous material having oxide ion conductivity and electron conductivity. The oxygen electrode layer 9 can be made of a composite material of one or more of (La,Sr)(Co,Fe)O3, (La,Sr)FeO3, La(Ni,Fe)O3, (La,Sr)CoO3, and (Sm,Sr)CoO3 and an oxide ion conductive material (such as GDC).
[0063] The porosity of the oxygen electrode layer 9 is not particularly limited, but may be, for example, 20% to 60%. The thickness of the oxygen electrode layer 9 is not particularly limited, but may be, for example, 1 μm to 100 μm.
[0064] The method for forming the oxygen electrode layer 9 is not particularly limited, and a baking method, a spray coating method, a PVD method, a CVD method, or the like can be used.
[0065] [Flow path member 30] The flow path member 30 is joined to the second main surface 13 of the metal support 10. The flow path member 30 forms a flow path 30a between itself and the metal support 10. A source gas is supplied to the flow path 30a. The source gas supplied to the flow path 30a is supplied to the hydrogen electrode layer 6 of the cell main body 20 through each communication hole 11 of the metal support 10.
[0066] The flow path member 30 can be made of, for example, an alloy material. The flow path member 30 may be formed of the same material as the metal support 10. In this case, the flow path member 30 may be substantially integral with the metal support 10.
[0067] The flow path member 30 has a frame 31 and an interconnector 32. The frame 31 is an annular member that surrounds the side of the flow path 30a. The frame 31 is joined to the second main surface 13 of the metal support 10. The interconnector 32 is a plate-like member for electrically connecting an external power source or another electrolysis cell to the electrolysis cell 1 in series. The interconnector 32 is joined to the frame 31.
[0068] In this embodiment, the frame 31 and the interconnector 32 are separate members, but the frame 31 and the interconnector 32 may be an integrated member. EXAMPLES
[0069] Examples of the electrolytic cell according to the present invention will be described below, but the present invention is not limited to the examples described below.
[0070] In this example, for the electrolytic cell according to the above embodiment, a number of test pieces (samples) were produced that had different combinations of "volume ratio of NiO in the hydrogen electrode layer 6," "type of ceramic material contained in the hydrogen electrode layer 6," "volume ratio of the ceramic material in the hydrogen electrode layer 6," "average particle size ratio R2 / R1 of NiO to the ceramic material in the hydrogen electrode layer 6," "opening ratio of the metal support 10," and "porosity of the hydrogen electrode layer 6."
[0071] Specifically, 39 types of samples were produced one by one, as shown in Table 1. In samples Nos. 1 to 13, Y2O3 was used as the ceramic material for the hydrogen electrode layer 6, in samples Nos. 14 to 26, YSZ was used as the ceramic material for the hydrogen electrode layer 6, and in samples Nos. 27 to 39, GDC was used as the ceramic material for the hydrogen electrode layer 6.
[0072] For each sample, the cell body 20 was formed by a sintering method on a stainless steel disk (diameter 10 cm, thickness 300 μm) serving as the metal support 10. As shown in Table 1, the aperture ratio of the metal support 10 was set for each sample. In the cell body 20, the thickness of the hydrogen electrode layer 6 was set to 200 μm, the thickness of the electrolyte layer 7 (8YSZ) to 5 μm, the thickness of the reaction prevention layer 8 (GDC) to 5 μm, and the thickness of the oxygen electrode layer 9 (LSCF) to 30 μm. As shown in Table 1, the porosity of the hydrogen electrode layer 6 was set for each sample.
[0073] In Table 1, the volume ratio, average particle diameter ratio R2 / R1, and porosity are measured values in the non-reduced state after firing and before reduction treatment. The volume ratio was calculated using one of the well-known methods using fluorescent X-rays. The average particle diameter R1, average particle diameter R2, average particle diameter ratio R2 / R1, and porosity were calculated by the method described in the above embodiment.
[0074] For the non-reduced (fired) bodies of each sample, a dimension (L1) of a predetermined location of the hydrogen electrode layer 6 before reduction treatment was measured at room temperature (normal temperature). Then, each sample was heated to 750°C and a reducing gas (hydrogen) was supplied to the hydrogen electrode layer 6 for 3 hours to perform a reduction treatment. Then, after each reduced body of the sample was cooled to room temperature, the dimension (L2) of the above-mentioned predetermined location of the hydrogen electrode layer 6 was measured again. The value (ΔL / L1) obtained by dividing the dimensional change amount ΔL (=L2-L1) before and after reduction treatment by L1 and multiplying it by 100 is shown in Table 1.
[0075] The fact that the fired body was transformed into a reduced body by the reduction treatment was confirmed by comparing the weights measured before and after the reduction treatment with the weights calculated from the volume ratios.
[0076] After the above-mentioned reduction treatment was performed on each sample, the presence or absence of cracks in the cross section of the hydrogen electrode layer 6 was confirmed by SEM. At this time, the presence or absence of microcracks that do not affect the characteristics of the hydrogen electrode layer 6 was also confirmed. Note that cracks with a length of 50 μm or less and a width of 0.5 μm or less were determined to be microcracks that do not affect the characteristics. The crack confirmation results are shown in Table 1. In Table 1, the case where no cracks were observed was evaluated as "◎", the case where only microcracks were observed was evaluated as "◯", and the case where cracks larger than microcracks were observed was evaluated as "X".
[0077] [Table 1]
[0078] As shown in Table 1, in samples in which the value of (ΔL / L1) × 100 was within ±0.05%, regardless of the type of ceramic material, the occurrence of cracks in the hydrogen electrode layer 6 was suppressed. This result was obtained because the difference in dimensional change between the portion of the hydrogen electrode layer 6 located directly above the communicating hole 11 and the other portion not directly above it was reduced.
[0079] Furthermore, as can be seen from a comparison of Samples Nos. 2, 10, and 11 with Samples Nos. 15, 23, and 24 and Samples Nos. 28, 36, and 37, by setting the aperture ratio of the metal support 10 to 5% or more, it was possible to further suppress the occurrence of cracks in the hydrogen electrode layer 6. This result was obtained because the reduction gas was uniformly supplied from the communicating holes 11 of the metal support 10 to the hydrogen electrode layer 6, thereby reducing unevenness in reduction between the directly above portion (the portion located directly above the communicating holes 11) and the non-directly above portion (the portion other than the directly above portion) of the hydrogen electrode layer 6.
[0080] Furthermore, as can be seen from a comparison of Samples Nos. 2, 12, and 13, Samples Nos. 15, 25, and 26, and Samples Nos. 28, 38, and 39, by setting the porosity of the hydrogen electrode layer 6 in a non-reduced state to 16% or more, it was possible to further suppress the occurrence of cracks in the hydrogen electrode layer 6. This result was obtained because the reduction gas was uniformly diffused in the hydrogen electrode layer 6, thereby reducing uneven reduction between the directly above and non-directly above portions of the hydrogen electrode layer 6. [Explanation of symbols]
[0081] 1 Electrolysis cell 10 Metal support 11 Communication hole 12 First main surface 13 Second main surface 20 Cell body 6 Hydrogen electrode layer 7 Electrolyte layer 8. Reaction prevention layer 9 Oxygen Polar Layer 30 Flow path member 30a Flow path
Claims
1. a metal support having a plurality of communicating holes formed on a main surface thereof; a cell body portion including a hydrogen electrode layer formed on the main surface and covering the plurality of communication holes, an oxygen electrode layer, and an electrolyte layer disposed between the hydrogen electrode layer and the oxygen electrode layer; Equipped with the hydrogen electrode layer is made of NiO and a ceramic material; When the dimension at room temperature of the hydrogen electrode layer in a reduced state obtained by subjecting the hydrogen electrode layer to a heat treatment in a reducing atmosphere at 750° C. is taken as L2, and the dimension at room temperature of the hydrogen electrode layer in a non-reduced state that has not been subjected to the heat treatment is taken as L1, the amount of change therebetween is taken as ΔL=L2-L1, where (ΔL / L1)×100 is within ±0.05%. Electrolysis cell.
2. The opening ratio of the plurality of communicating holes in the main surface is 5% or more.
2. The electrolysis cell of claim 1.
3. the porosity of the hydrogen electrode layer in the non-reduced state is 16% or more; 3. An electrolytic cell according to claim 1 or 2.
Citation Information
Patent Citations
Electrochemical cell
JP2020155337A